Very-high-power Short-duration Ablation versus Conventional Ablation for Pulmonary Vein Isolation in Atrial Fibrillation: Systematic Review and Meta-analysis - Raymond Pranata; Giky Karwiky; Mohammad Iqbal (Arrhythmia & Electrophysiology Review)
The aim of this study was to compare the effectiveness and safety of very-high-power short-duration (VHPSD) ablation (70–90 W/4–7 s) with conventional ablation (30–40 W/>20 s, 50 W/7–11 s) for pulmonary vein isolation (PVI) in patients with AF. A total of 13 studies were included in this analysis (1,527 patients). AF recurrence occurred in 14% (95% CI [11–18%]) of the VHPSD group. VHPSD was associated with lower AF recurrence (OR 0.65; 95% CI [0.48–0.89]; p=0.006) compared with the conventional ablation group. Subgroup analysis showed that additional ablation beyond PVI had a similar rate of AF recurrence (16% versus 10%) compared with PVI alone. Procedure and ablation durations were significantly shorter in the VHPSD group with a mean differences of –14.4 minutes (p=0.017) and −14.1 minutes (p<0.001), respectively. Complications occurred in 6% (95% CI [3–9%]) of the VHPSD group, and the rate was similar between the two groups (OR 1.03; 95% CI [0.60–1.80]; p=0.498). VHPSD ablation resulted in less AF recurrence and a shorter procedure time. Additional ablation beyond PVI alone in VHPSD may not provide additional benefits.